2008
DOI: 10.1073/pnas.0710344105
|View full text |Cite
|
Sign up to set email alerts
|

Quorum decision-making facilitates information transfer in fish shoals

Abstract: Despite the growing interest in collective phenomena such as ''swarm intelligence'' and ''wisdom of the crowds,'' little is known about the mechanisms underlying decision-making in vertebrate animal groups. How do animals use the behavior of others to make more accurate decisions, especially when it is not possible to identify which individuals possess pertinent information? One plausible answer is that individuals respond only when they see a threshold number of individuals perform a particular behavior. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
417
3
8

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 420 publications
(437 citation statements)
references
References 28 publications
9
417
3
8
Order By: Relevance
“…However, in contrast to some recent studies (e.g. Ward et al 2008;Franks et al 2009;Sumpter & Pratt 2009 did not find evidence that consensus decisions followed a quorum decision rule. Kerth et al (2006) found that Bechstein's bats, Myotis bechsteinii, can make group roost decisions that follow a majority rule.…”
Section: Discussioncontrasting
confidence: 98%
“…However, in contrast to some recent studies (e.g. Ward et al 2008;Franks et al 2009;Sumpter & Pratt 2009 did not find evidence that consensus decisions followed a quorum decision rule. Kerth et al (2006) found that Bechstein's bats, Myotis bechsteinii, can make group roost decisions that follow a majority rule.…”
Section: Discussioncontrasting
confidence: 98%
“…Recent experiments in simplified laboratory environments have demonstrated that the wisdom of crowds can improve decision accuracy across a variety of contexts, including avoiding a replica predator [22,23] and discriminating between conspecific phenotypes [24], suggesting that this may be an important driver favouring the evolution of sociality. Nonetheless, it is evident in nature that many organisms make decisions alone, and that many social organisms live in relatively small groups [25], seemingly failing to take advantage of the informational benefits of large group size.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, although they may lack the capacity for numerosity (the ability to explicitly count or tally), or to explicitly cast a 'vote', organisms such as schooling fish do effectively perform majority consensus decision-making through their employment of simple and local social interactions [15,[22][23][24]39]. Furthermore, the presence of individuals lacking preferences has been shown to further promote majority voting by such animal groups [39].…”
Section: Introductionmentioning
confidence: 99%
“…In general, as long as they are consistent with phenomenology, simple models of communication are preferred to more complex descriptions [12] because they are more elegant and depend on fewer assumptions. Such simple descriptions, often referred to as swarm models, have been highly useful in recounting collective patterns within a wide variety of species, including fishes, birds, locusts and other social insects [4,[13][14][15]. They use mathematical modelling to show how the observed large-scale experimental phenomena emerge from a small set of proposed behavioural rules.…”
Section: Introductionmentioning
confidence: 99%